2020
DOI: 10.3390/app10196996
|View full text |Cite
|
Sign up to set email alerts
|

The Invasion of Bacterial Biofilms into the Dentinal Tubules of Extracted Teeth Retrofilled with Fluorescently Labeled Retrograde Filling Materials

Abstract: In this study, we evaluated the invasion of bacteria into the dentinal tubules of retrofilled extracted human teeth, and the influence of different fluorescently labeled retrograde filling materials on the bacterial invasion and viability, by means of confocal laser scanning microscopy (CLSM). The root apices of extracted teeth were cut, prepared, and filled retrogradely using either intermediate restorative material (IRM), mineral trioxide aggregate (MTA), or Biodentine. The roots were filled with Enterococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
(93 reference statements)
1
10
0
Order By: Relevance
“…Our results reveal a pattern of bacterial invasion and lling penetration in which the buccolingual direction was preferred to the mesiodistal direction, regardless of the lling material. This nding is in accordance with the results of previous investigations [10,14,48]. The deeper penetration of both the lling material and bacteria in the buccolingual direction may be associated with an anatomicalphysiological phenomenon termed "the butter y effect," which refers to the butter y-like appearance observed on the cross-sections of roots as a result of higher sclerosis in the tubuli at the distal and mesial sides of the root canal [32,49,50].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results reveal a pattern of bacterial invasion and lling penetration in which the buccolingual direction was preferred to the mesiodistal direction, regardless of the lling material. This nding is in accordance with the results of previous investigations [10,14,48]. The deeper penetration of both the lling material and bacteria in the buccolingual direction may be associated with an anatomicalphysiological phenomenon termed "the butter y effect," which refers to the butter y-like appearance observed on the cross-sections of roots as a result of higher sclerosis in the tubuli at the distal and mesial sides of the root canal [32,49,50].…”
Section: Discussionsupporting
confidence: 91%
“…CLSM is a valuable modality of choice alongside more traditional SEM and PCR-based techniques to identify viable bacteria in dentinal tubules [10,[12][13][14][15]. Importantly, using CLSM with the live/dead staining method allows us to assess the extent of contamination and vitality of bacteria in the dentinal tubules [10,[12][13][14][15]. No study has used CLSM to evaluate the bacterial colonization in VRF of extracted human teeth lled with different materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimal and maximal bacterial penetration depths into the dentinal tubules were 1 µm and 1480 µm, respectively, with a mean of 167 µm. 39 Thus, a complementary/supportive technique to increase the effectiveness of root canal treatment is needed. 40 The average biofilm degradation in the PDT-only group (0.78) was lower than the control group (1.06).…”
Section: Discussionmentioning
confidence: 99%
“…aPDT is not an exception as the light propagation and PS penetration inside dentinal tubules are restricted. Moreover, reports have shown that bacteria can migrate into dentinal tubules up to a depth of 1,000 μm, where oxygen as a vital component of aPDT is absent ( Balhaddad et al, 2020 ; Rosen et al, 2020 ). To overcome these issues, some studies used hydrogen peroxide solution that provided pre-treatment of the biofilm, resulting in better PS penetration and increased available oxygen in the environment ( Garcez et al, 2011 ; Garcez and Hamblin, 2017 ).…”
Section: Applications Of Antimicrobial Photodynamic Therapy In Endodo...mentioning
confidence: 99%